Sodium hydroxide and potassium hydroxide levels in noodles and their effects on flavor, color, and tenacity - Abadiano, Marietta C. 1941- (1961)
The purpose of this study is to find out the suitability of alkalies like sodium hydroxide and potassium hydroxide in increasing the quality of noodles by increasing gluten development and tenacity, and the highest level of alkali which may be added that will have the least detectable effects on palatability and flavor.